Optimalisasi Peran Petugas Lembaga Pemasyarakatan dalam Menangani Konflik Antar Narapidana - Silistiawati, Ira; Rahmayanti; Audina, Karina; Nst, Siti Ellyza Sari; Wingcun, Wingcun (Innovative: Journal Of Social Science Research, 2025)
Correctional Institutions (Lapas) are institutions that not only function as a place for carrying out criminal acts, but also as a place for fostering prisoners. However, the heterogeneity of social, cultural, and character backgrounds of prisoners often triggers conflicts within the prison environment. Conflicts between prisoners can disrupt security stability and hinder the fostering process that should run conducively. Therefore, the role of Correctional Institution officers is very important in preventing, handling, and resolving conflicts that occur. This article aims to analyze the role of prison officers in handling conflicts between prisoners and formulate strategies to optimize these roles. The research method used is qualitative with a literature study approach and interviews with a number of prison officers. The results of the study indicate that optimizing the role of officers can be done by improving communication competencies, mediation, and understanding of the psychological dynamics of prisoners, as well as the formation of a conflict management team in the prison environment. Thus, it is hoped that a safer and more conducive atmosphere will be created to support the fostering process within the prison.